Growth and Gut Morphology of Diploid and Triploid Juvenile Atlantic Cod (Gadus morhua) - Vargas, Cecilia; Hagen, Ørjan; Solberg, Christel; Jobling, Malcolm; Peruzzi, Stefano (Aquaculture Research, 2014)
The objective of this paper was to compare the growth and gut morphology of juvenile diploid and triploid Atlantic cod (Gadus morhua) reared under similar conditions. Individually tagged 36-week old diploid (mean weight 49.3 ± 13.8 g) and triploid (mean weight 43.6 ± 11.2) juvenile cod were measured at intervals during a 29-weeks growth trial. Data for weight, length, condition factor (K), hepato-somatic index (HSI), gonado-somatic index (GSI), Relative Gut Length (RGL), and pyloric caeca number were collected and results were analyzed in relation to ploidy status, gender and family contribution. At the end of the experiment, only one family (M2xF3) had many representatives with a relatively even distribution of sexes and ploidies. Diploid females were significantly heavier and had higher K than triploid females in the M2xF3 family (body weight 371.2 ± 120.2 vs. 298.4 ± 100.7g; K 1.1 ± 0.1 vs. 0.93 ± 0.1) but no differences were found between diploid and triploid males. In the other families (pooled data), no differences in body weight were found between the ploidy groups. In general, triploids had a shorter intestine (RGL) and fewer pyloric caeca than their diploid siblings regardless of gender suggesting possible impairments in nutrient utilization and growth.